Extract [videorecording (DVD)] - Judge, Mike; Affleck, Ben, 1972-; Simmons, J. K.; Bateman, Jason; Kunis, Mila, 1983- (Miramax Films : Buena Vista Home Entertainment, 2011)
Joel is one step away from selling his flavor extract factory and retiring to easy street when a freak workplace accident sets in motion a series of disasters that puts his business and personal life in jeopardy.